Physical demands on professional Spanish football referees during matches - Martinez-Torremocha, G.; Martin-Sanchez, M. L.; Garcia-Unanue, J.; Felipe, J. L.; Moreno-Perez, V.; Paredes-Hernandez, V.; Gallardo, L.; Sanchez-Sanchez, J. (Science and Medicine in Football, 2023)
Background: Refereeing is a demanding and intermittent activity that combines high-speed and low-intensity action Objective: The aim of this study is to analyse the external and internal load of professional Spanish football referees during matches, and to compare the physical demands between halves and between referees in different categories Methods: The physical demands on 40 professional football referees from the first and second divisions were recorded using global positioning system (GPS) technology and heart rate bands. External load (distance covered, speed, acceleration and deceleration) and internal load (perceived exertion [RPE] and heart rate [HR]) were analysed Results: The referees in the first division reported lower mean HR and RPE results than those in the second division (p < 0.05). The total distance covered was similar between the categories (p > 0.05), but the distance covered at different speed ranges was different (p < 0.05). Finally, greater reductions in performance between the first and the second halves were found in the second division referees (p < 0.05) Conclusions: The results of this study show differences according to the category of referee. This emphasises the need for specific training for professional referees according to their level to ensure optimal performance during matches.